CONCEPTUAL MODELE OF THE FINANCIAL CONTROLLING SYSTEM ORGANIZATION ON INDUSTRIAL ENTERPRISE - Боярко , Ірина; Гриценко , Лариса; Рябенков , Олексій (Socio-economic relations in the digital society, 2019)
The article is devoted to the development of theoretical and methodological background for the financial controlling system organization through the effective use of the financial potential of industrial enterprises. Conceptual basis of the financial controlling system is developed. The understanding of scientific views of the economic meaning of «controlling» and «financial controlling» was generalized in the article. Understanding of financial controlling essence is deepened. The essential characteristics of financial controlling were selected. The specific features of controlling strategic focus in the financial management of the company were investigated. The necessity of organization and implementation of financial controlling as an instrument of economic management in the company in the long term was proved.